2020
DOI: 10.1115/1.4044854
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Metamaterial-Based Foundation for Fuel Storage Tanks and Experimental Evaluation of Its Effect on a Connected Pipeline System

Abstract: The recent advance of seismic metamaterials has led to various concepts for the attenuation of seismic waves, one of them being the locally resonant metamaterial. Based on this concept, the so-called metafoundation has been designed. It can effectively protect a fuel storage tank from ground motions at various fluid levels. In order to show the effectiveness of the proposed design, the response of the metafoundation is compared to the response of a tank on a traditional concrete foundation. The design process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Metafoundations, on the other hand, are placed beneath the structure as a support system, thus bearing its weight. In a structural-focused direction, Wenzel et al [27] study the protection of storage tanks with the use of resonant metafoundations clearly revealing the attenuation capabilities in the resulting stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Metafoundations, on the other hand, are placed beneath the structure as a support system, thus bearing its weight. In a structural-focused direction, Wenzel et al [27] study the protection of storage tanks with the use of resonant metafoundations clearly revealing the attenuation capabilities in the resulting stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Eurocode 3 and 8, [14,15]). Besides this, an experimental study on the coupling e↵ects between a tank isolated with a metamaterial-based foundation and a pipeline suggested that this type of foundation may provide a compromise between base shear attenuation and horizontal displacement [16], which is a property that cannot be obtained with classical isolation systems.…”
Section: Introductionmentioning
confidence: 99%
“…From their review one can clearly conclude that one of the most pressing problems of metamaterial-based foundations is the excessive size necessary to obtain a functional foundation. However, two advantages may become attainable through such foundations in future, namely: (i) attenuation of the vertical component [5] and rocking motions [20], which cannot be addressed by traditional base isolation systems [21]; and (ii) a compromise between base shear reduction and horizontal displacement [16]. One idea to improve the performance of a metamaterial-based system was proposed by Antoniadis et al [22] who showed that a negative sti↵ness element (NSE) inserted in the resonator mechanism could potentially improve the system behaviour significantly.…”
Section: Introductionmentioning
confidence: 99%